The Tasks and the Crossroads of Sociology of Art - Gaižutis, Algirdas (Sociologija. Mintis ir veiksmas, 1997)
The article aims to discuss the sociology of art and its problematique. Considerations are being made about the relation between the sociology of art and philosophy. While sociological analysis tends to discuss the relationship of art with its social context, the object of analysis itself does not allow to settle with such a description. Central to the sociology of art are the questions of meaning, which appear especially important in the periods of transformation of social reality.
Keywords: sociology of art; art; meaning